Urgensi Pengaturan Larangan Penyebaran Konten Bunuh Diri di Media Sosial Dalam Hukum Positif di Indonesia (RechtJiva, 2024)
This research addresses the issue of Criminalization of Suicide Content Spread on Social Media. Indonesia is one of the countries with a suicide rate reaching 1.12 per 100,000 population. Suicide is believed to be contagious, especially among individuals with similar backgrounds to the suicide victim, necessitating suicide postvention to reduce the risk of copycat suicides. This imitation effect is known as suicide contagion or The Werther Effect. The 2024 Amendment to Law Number 11 Year 2008 concerning Electronic Information and Transactions is expected to protect Indonesian society from the negative impacts of technological advancements. Based on these points, this paper formulates the following research questions: (1) Are there regulations prohibiting the dissemination of suicide content in Indonesia? (2) What are the future legal regulations concerning the prohibition of disseminating suicide content in Indonesia? This study employs a juridical-normative method with a legislative approach and comparative approach. The findings indicate that disseminating suicide content is hazardous, supported by psychologists confirming that suicide can spread even through social media content alone. Currently, there are no specific articles in the ITE Law that can prosecute disseminators. Therefore, preventive efforts are needed to minimize the high suicide rates caused by exposure to suicide content on social media, thereby fulfilling the law's role as social control.